Implementation of Circular Economy in Strengthening Sustainable Agribusiness: Systematic Literature Review - Nugroho, Anton (JURNAL AGRIBISAINS, 2025)
The agribusiness sector faces complex challenges, ranging from high volumes of production waste, dependence on limited natural resources, to pressures on environmental sustainability and food security. The still-dominant linear business model worsens this condition, while the implementation of Circular Economy (CE) has not been systematically integrated into the agribusiness value chain. This study aims to analyze the application of CE principles in strengthening sustainable agribusiness through a Systematic Literature Review. The research approach refers to PRISMA (2020) guidelines and the PICo framework (Population, Interest, Context) to ensure the accuracy of literature selection. A total of 26 selected scientific publications were thematically analyzed using the Triple Bottom Line framework (Economic, Social, Environmental) and Resource-Based View perspective. The analysis results indicate that the implementation of CE at every stage of the agribusiness value chain—from production, processing, to distribution—provides significant contributions to resource efficiency, waste reduction, and ecosystem regeneration. The main driving factors for implementation include policy support, technological innovation, and consumer awareness toward sustainable products. Conversely, the main barriers include limited technical capacity of smallholder farmers, digital divide, and weak coordination among stakeholders. Conceptually, this study generates an integrative model showing that CE success is determined by the configuration of valuable resources, rare capabilities, and collaborative relationships that are difficult to imitate. This research confirms that CE is not only a technical strategy, but a development paradigm for agribusiness oriented toward innovation, social inclusiveness, and long-term resilience.